2014
DOI: 10.1177/0954411914528307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 addition on surface microstructure and bioactivity of fluorapatite coatings deposited using Nd:YAG laser

Abstract: To study the effect of titania (TiO2) addition on the surface microstructure and bioactivity of fluorapatite coatings, fluorapatite was mixed with TiO2 in 1:0.5 (FA + 0.5TiO2), 1:0.8 (FA + 0.8TiO2), and 1:1 (FA + TiO2) ratios (wt%) and clad on Ti-6Al-4V substrates using an Nd:YAG laser system. The experimental results show that the penetration depth of the weld decreases with increasing TiO2 content. Moreover, the subgrain structure of the coating layer changes from a fine cellular-like structure to a cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…5, some ions still remain within the CL. It is noted, however, that some of the P ions produced in the FA decomposition process simply vaporize in the high-temperature cladding process [21,22]. Observing the results presented in Fig.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…5, some ions still remain within the CL. It is noted, however, that some of the P ions produced in the FA decomposition process simply vaporize in the high-temperature cladding process [21,22]. Observing the results presented in Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Many studies have shown that laser cladding enhances the bonding strength between bioceramic materials such as HA and FA and metallic substrates and hence inhibits the disintegration and detachment of the coating layer [21][22][23][24][25]. In a previous study [22], the present group investigated the effects of TiO 2 addition on the surface microstructure and bioactivity of FA coatings deposited on Ti6Al4V substrates using an Nd:YAG laser.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nonetheless, as shown in Figure 9, some ions still remain within the CL. It is noted, however, that some of the P ions produced in the FA decomposition process simply vaporize in the high-temperature cladding process [37,38,39,40]. Observing the results presented in Figure 9, it is seen that the distributions of Zr in the CL and TL, respectively, are roughly the same.…”
Section: Resultsmentioning
confidence: 83%
“…Consequently, the present study investigates the microstructural properties and phase composition of composite FA coatings containing 20 wt % yttria (3 mol %) stabilized zirconia (ZrO 2 , 3Y-TZP) deposited on Ti6Al4V substrates using a laser-cladding technique. As in previous studies by the present group [38,39,40], the laser cladding process is performed using an Nd:YAG laser system.…”
Section: Introductionmentioning
confidence: 99%